تأثير برنامج ترقية اللغة الأجنبية في ترقية مهارة الكلام لطلاب الجامعة في كلية التربية بجامعة الإسلامية الحكومية - El-Nabila, Syafiqoh; Maisaroh, Siti (AS-SABIQUN, 2024)
This research is based on the existence of a language development program which we often know as FLDP (Foreign Language Development Program), which is one of the programs offered and presented by the Madura State Islamic Religious Institute campus to prepare students for the future. This research aims to measure the influence of IAIN Madura's FLDP (Foreign Language Development Program). This type of research is quantitative. Data collection techniques use questionnaires, observation and documentation. In the aspect of developing speaking skills, it is very necessary, especially for foreign speakers, so IAIN Madura presents FLD (Foreign Language Development Program) so that IAIN Madura students are not only able to think but are also able to speak Arabic.